The Effect of Mammalian Target of Rapamycin Versus Calcineurin Inhibitor–based Immunosuppression on Measured Versus Estimated Glomerular Filtration Rate After Orthotopic Liver Transplantation. Issue 6 (June 2015) - Zitta, Sabine; Schaffellner, Silvia; Gutschi, Jürgen; Meinitzer, Andreas; Kniepeiss, Daniela; Artinger, Katharina; Reibnegger, Gilbert; Rosenkranz, Alexander R.; Wagner, Doris
<x xml:space="preserve">Abstract</x> Introduction Mammalian target of rapamycin (mTOR) inhibitors have been proposed to preserve renal function in patients after orthotopic liver transplantation (OLT) based on estimated glomerular filtration rate (eGFR). The presented study evaluated their effect on renal function in comparison to calcineurin inhibitors (CNIs) defined by measured GFR. Methods Renal function was measured in patients on mTOR-based (n=28) or on CNI-based (n=51) immunosuppression after OLT by performing inulin clearance (IC) as well as eGFR based on the Modification of Diet in Renal Disease (MDRD4) Study and the chronic kidney disease epidermiology (CKD-EPI) formula at baseline, 6, 12, 18, and 24 months. Statistical analysis was performed by using analysis of variance and serial measurement testing. Results The MDRD4 and the IC values differed significantly at study inclusion in both groups (mTOR and CNI group, P=0.001), whereas the CKD-EPI and the IC values did not. Estimated GFR by the MDRD4 results declined throughout the study period in patients on CNI and in patients on mTOR (CNI, 81 vs. 61 mL/min/1.73 m2, P=0.01; 82 vs. 60 mL/min/1.73 m2, P=0.01), whereas CKD EPI and measured GFR did not change throughout the study period in the CNI. Conclusion The use of eGFR especially the MDRD-based formula, in OLT patients, leads to incorrect interpretation of their renal function.